Climate Resilient Rainfed Agriculture status and strategies - Rao, Ch. Srinivas; Gopinath, K. A.; Prasad, Y. G.; Sikka, A. K.; Singh, Rajbir (Indian Farming, 2016)
Droughts and famines are the general features of rainfed agriculture in India. The risk involved in successful cultivation of crops depends on the nature of drought (chronic and contingent); its probable duration, and periodicity of occurrence within the season. These aberrations are likely to further increase in future. There are a number of options in soil, water and nutrient management technologies which contribute to both adaptation and mitigation. Much of the research done in rainfed agriculture in India relates to conservation of soil and rainwater, and drought proofing which is an ideal strategy for adaptation to climate change. However, successful adaptation to climate change and technology up scaling require long-term investments in strategic research and new policy initiatives that mainstream climate change adaptation into development planning.